An Empirical Study on the Factors Influencing Usage of Mobile Payments with Reference to Bangalore City - Mr. Mahabub Basha S; Dr. Kethan M; Dr. Rajasulochana A.L (HM Journals, 2023)
Mobile banking can be explained as a channel over which the customers interact with a bank using a mobile phone; apparently this can be any digital assistant of any form. Mobile banking assists an individual to perform transactions from remote places and even know account details at a very low cost. Going a step forward, UPI and mobile payments also allow the individual to perform same task using a mobile phone, any time anywhere. In the present times mobile payments and adoption of the same are very common in urban and semi-urban areas, but still there are some issues related to the usage and adoption of the same by a number of users. This present study will try to find out the gaps and analyse the situation with a sample of 200 respondents from government housing societies of Bangalore City. This study is based on primary data and uses one way ANOVA to analyse the data. Findings of the study will certainly add to the ongoing studies and future researchers.